Almas integradas: Política educacional, Educação Moral e Cívica e formação do cidadão na ditadura militar (Brasil-1964/1974) - Santos, Marcelo Gonzaga dos (Universidade Federal de São Carlos, 2013)
Completed nearly half a century to the advent of the military coup, it is necessary to the resumption of a reflection on the impact of the military regime in the Brazilian education. Although the conquest of the State of democratic law have achieved more than twenty years, the legacy of the military dictatorship educational public policy and, even, about the social imaginary is still present. Some brands of the impact of the military regime in Brazilian education are, even today, Government speeches and us candied policy proposals of attendance at educational demands, such as: the linking of public education to the interests and needs of the market; investment in the private sector and encouraging voluntarism, to meet the responsibility of the State; the quantitative expansion of public education, with compromised quality and low cost for the Government; imposing the use of materials and teaching resources by the State; and the disqualification of teachers. The purpose of this study is, through the authoritarian political discourse on education and its embodiment in public policy, understand how the implementation of moral discipline and civic. The main source of this research is the magazine Documents, Official Journal of the federal Government. Starting from the analysis of laws, decrees, opinions, speeches and articles published in the magazine Documents, seeks to understand the implementation of public policies aimed at educational and Civic Moral education. Knowing of the legacy that the authoritarian State left for the Brazilian society, is considered essential to revisit some aspects of educational policy deployed during this period, because the more we understand the past, more clearly sees this.
Integrated souls: Educational Policy, Moral and Civic Education and Citizen Training in Military Dictatorship (Brazil-1964/1974)
Keywords: Educação moral e cívica; Ditadura militar; Formação do indivíduo conteúdo escolar; Civismo; Civility; Civil - military dictatorship; Moral and civic education; Training of the individual; CIENCIAS HUMANAS::EDUCACAO